Optimization of DNA Extraction Methods in Fresh Meat (Rat and Chicken Meat) based on Incubation Time - Sunaryo, Hadi; Wirman, Adia Putra; Permanasari, Etin Diah; Nikmatullah, Nurul Azmah; Lestari, Dian; Nurjanah, Desi (UIN Sunan Gunung Djati Bandung, 2023)
DNA (deoxyribonucleic acid) extraction method is the process of separating DNA from the sample. In this process, the DNA obtained must be protected from contamination by RNA, carbohydrates, lipids, and proteins. Contamination of RNA, carbohydrates, lipids, and proteins can increase DNA purity. DNA purity was measured using a NanoDrop 2000 spectrophotometer measured by the absorbance ratio at 260 nm and 280 nm wavelengths. Good quality DNA will have an A260/A280 ratio of 1.7-2.0 and a concentration > 0.03 pg. This study aimed to obtain the appropriate DNA extraction method for fresh meat samples (a mixture of rat and chicken meat). This research consisted of two stages: the DNA extraction stage using the Progenus EasyFast™ Extraction Kit for Meat Products and the amplification stage using the EASYFAST™ Rat Detection Kit. This study used 16 samples of a mixture of rat meat and chicken with concentrations of rat meat: 5, 10, 15, and 20%. At the extraction stage, the incubation time was optimized for 15, 30, 45 minutes, and 1 hour. The results showed that the one hour incubation had a lowest CT value in the results of PCR amplification.